2013
DOI: 10.1037/a0031366
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of protective behavioral strategies: Comparing the absolute frequency and contingent frequency response scales.

Abstract: The purpose of the present studies was to examine the effects of response scale on the observed relationships between protective behavioral strategies (PBS) measures and alcohol-related outcomes. We reasoned that an ‘absolute frequency’ scale (stem: “how many times…”; response scale: 0 times to 11+ times) conflates the frequency of using PBS with the frequency of consuming alcohol; thus, we hypothesized that the use of an absolute frequency response scale would result in positive relationships between types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The problem of conflated PBS use with frequency of drinking has already been identified in the literature (Kite et al, 2013; Pearson, 2013; Pearson et al, 2012; Prince et al, 2013). However, by controlling for the number of drinking occasions in postsurvey calculations rather than in the stem of the item, the current adjustment allows for a more precise measure of PBS use (e.g., specific number of times) rather than broad categories (e.g., never, sometimes, always ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The problem of conflated PBS use with frequency of drinking has already been identified in the literature (Kite et al, 2013; Pearson, 2013; Pearson et al, 2012; Prince et al, 2013). However, by controlling for the number of drinking occasions in postsurvey calculations rather than in the stem of the item, the current adjustment allows for a more precise measure of PBS use (e.g., specific number of times) rather than broad categories (e.g., never, sometimes, always ).…”
Section: Discussionmentioning
confidence: 96%
“…This indicates the explanation for these inconsistent findings may lie in the response scale rather than the content the items used. To determine whether the differences in the estimated associations between PBS and alcohol use between the SQ (often used with absolutely frequency responses) and the PBSS (often used with contingent frequency responses) were due to the content of the items or the type of response scale, Kite and colleagues (2013) added the alternative response scale options to the traditional administration. They found that contingent response options yielded the expected negative associations between PBS and alcohol use and problems, regardless of whether the SQ or the PBSS was used.…”
Section: Inconsistent Pbs Relationships and Response Scalesmentioning
confidence: 99%
“…It is important to note that some of these studies included multiple samples (Benton et al, 2007; Kite, Pearson, & Henson, 2013) and some of the samples were used in multiple reports (e.g., Harris, Walters, & Leahy, 2008; Walters, Roudsari, Vader, & Harris, 2007; Walters, Vader, Harris, & Field, 2009; Walters, Vader, Harris, & Jouriles, 2009), so it is difficult to know exactly how many independent samples were reported across these studies.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Finally, the yes/no responses were used to describe the use of each PBS on a specific day or occasion. Considering the effects of these variations on validity is important because previous work has demonstrated strong concurrent validity of PBS use when assessed using a contingent frequency response scale, but not with an absolute frequency response scale (Kite, Pearson, & Henson, 2013). Presumably, this difference occurs because an absolute frequency response scale conflates frequency of alcohol use with frequency of PBS use.…”
Section: Measurement Of Pbsmentioning
confidence: 99%
See 1 more Smart Citation